2019
DOI: 10.1007/s00125-019-4918-x
|View full text |Cite
|
Sign up to set email alerts
|

Locally delivered GLP-1 analogues liraglutide and exenatide enhance microvascular perfusion in individuals with and without type 2 diabetes

Abstract: Aims/hypothesis Glucagon-like peptide-1 (GLP-1) analogues reduce the risk of macrovascular disease in diabetes; however, little is known about their microvascular effects. This research examined the microvascular actions of the GLP-1 analogues liraglutide and exenatide in individuals with and without type 2 diabetes (study 1). It also explored the involvement of the GLP-1 receptor (study 2) and the nitric oxide pathway in mediating the microvascular effects of the analogues. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…In support of these studies, it has also been established that LIRA increases NO-bioavailability in the vasculature in other disease states including arterial stenosis [33]. Further, Aung et al [34] recently showed that local delivery of LIRA increased skin microvascular perfusion in diabetic subjects and increased supernatant nitrate concentration and eNOS phosphorylation in human microvascular endothelial cell (HCMEC/D3 cell line) culture. Taken together, these findings suggest that it is reasonable to conclude that the improvement in coronary microvascular perfusion that we observed in LIRA treated obese Zucker rats is in part due to increased coronary NO production.…”
Section: Discussionmentioning
confidence: 88%
“…In support of these studies, it has also been established that LIRA increases NO-bioavailability in the vasculature in other disease states including arterial stenosis [33]. Further, Aung et al [34] recently showed that local delivery of LIRA increased skin microvascular perfusion in diabetic subjects and increased supernatant nitrate concentration and eNOS phosphorylation in human microvascular endothelial cell (HCMEC/D3 cell line) culture. Taken together, these findings suggest that it is reasonable to conclude that the improvement in coronary microvascular perfusion that we observed in LIRA treated obese Zucker rats is in part due to increased coronary NO production.…”
Section: Discussionmentioning
confidence: 88%
“…The metabolic benefits of the exenatide are correlated with the activation of VEGF-A-mediated angiogenesis and alleviate hypoxia in AT [ 78 ]. In line with animal studies, a recent clinical study reported that exenatide increased the vascularization of AT in obese diabetic patients to improve blood glucose levels and insulin sensitivity [ 79 , 80 ]. Therefore, activation GLP-1 R may facilitate AT vascularization, and then improve AT chronic hypoxia to alleviate obesity and obesity-related metabolic disturbance.…”
Section: Adecs: the Gatekeeper Of Adipocyte Metabolismmentioning
confidence: 88%
“…GLP-1 analogs represent a unique class of antidiabetic peptide drugs with potential clinical benefits over existing therapies for T2DM treatment [32]. Lira, a lipophilic long-acting GLP-1 analog, is still subcutaneously administered.…”
Section: Discussionmentioning
confidence: 99%